Rapid public health genomics capacity building during the COVID-19 Delta crisis driven by a transnational private, public, and social alliance - Mehul Champaklal Mehta; Mehul Champaklal Mehta; Mehul Champaklal Mehta; Gayatri Nair Lobo; Gayatri Nair Lobo; Gretchen Weightman; Gretchen Weightman; Vidushi Chitalia; Vidushi Chitalia; Jayanthi Shastri; Jayanthi Shastri; Jayanthi Shastri (Frontiers in Public Health)
When the COVID-19’s Delta variant spread globally during late 2020, Public Health Genomics (PHG) capabilities were missing in several cities, significantly impairing the ability of policymakers and public health systems to rapidly identify COVID-19 variants and effectively respond, with tragic human and economic consequences. In this community case study, we retrospectively studied the dire situation during the Delta wave 5 years ago when we rapidly constituted a transnational public, private, and social, pro-bono alliance to establish PHG capabilities in Mumbai, a mega metropolis that lacked this capacity. The Albright Stonebridge Group—a renowned global commercial diplomacy entity, Illumina—a genomic sequencing equipment leader, a leading Mumbai non-governmental organization—the ATE Chandra Foundation, and the Municipal Corporation of Greater Mumbai, came together in an alliance to rapidly establish PHG capabilities in Mumbai. This effort was coordinated across multiple countries, with distributed decision-making and defined responsibilities. An optimal site for a PHG center in Mumbai was identified, and the operational requirements, governance structures, resource and sustainability requirements were defined. In 3 months, the Genome Sequencing Centre for Outbreak Preparedness & Epidemiology (GeSCOPE) was successfully established in Mumbai’s public infectious disease hospital, Kasturba. The percentage of samples sequenced increased from less than 1% to over 30%, including all known RT-PCR positive cases, the sequencing time dropped to under 72 h, and public health policy and responses were enhanced. Currently, GeSCOPE has established itself as the epidemiological hub for Mumbai and western India at large, identifying infectious disease threats such as Dengue, Chikungunya, and drug resistance genes in Mycobacterium tuberculosis strains. This has transformed Mumbai’s ability to expeditiously identify and contain infectious outbreaks, thus better protecting its citizens. Our experience has generalizable lessons that we hope will inform other communities seeking to establish and strengthen their PHG capabilities.